The Relationship of Implementation of The Electronic Prescription System on User Satisfaction in General Hospital Royal Prima Medan - Jaska ran Dhillon; Chrismis Novalindan Ginting; Sri Wahyuni Nasution (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
The use of ICT is also utilized in the health sector to increase the effectiveness of services to the community. Electronic prescriptions have been widely used in hospitals to replace manual prescriptions. In several studies, electronic prescriptions are said to have many advantages, including reducing the incidence of prescribing errors. The location of study is General Hospital Prima Medan. The aim of this research is to determine the relationship between the implementation of an electronic prescription system and user satisfaction at General Hospital Royal Prima Medan. The type of research used in this research is descriptive correlational using a quantitative approach at General Hospital Royal Prima Medan and this study was 137, divided into 124 doctors and 40 pharmacy officers. The data analysis used in this research is univariate analysis and bivariate analysis. Data analysis in this study used univariate, bivariate, multivariate analysis using the SPSS Version 25 statistical application. The research results showed that a significant relationship between the implementation of the electronic prescription system and user satisfaction at General Hospital Royal Prima Medan with a very strong level of relationship, and this correlation is significant because p < 0.05 (0.000 < 0.05), So it can be concluded that there is a relationship between the implementation of the electronic prescription system and user satisfaction at General Hospital Royal Prima Medan. The results of research regarding the relationship between the implementation of the electronic prescription system and user satisfaction at General Hospital Royal Prima Medan which has been carried out show that 110 respondents said the implementation of electronic prescriptions at General Hospital oyal Prima Medan was good with a percentage of 80.3%, 27 respondents were not doing well with a percentage of 19.7% of the total respondents in this study of 137 respondents. Keywords: Electronic, Hospital, Implementation, Prescriptions, Satisfaction